NPC1 trafficking via VPS41-dependent LAMP carriers regulates endosomal cholesterol homeostasis - Klevis Ndoj; Matteo Tantucci; Paolo Sanza; Kristian Zubak; Giorgia Marodin; Jenina Kingma; Felix Snijder; Tineke Veenendaal; Daniel L. Kober; Noam Zelcer; Judith Klumperman (Proceedings of the National Academy of Sciences, 2025)
The Niemann-Pick type 1 and 2 proteins (NPC1 and NPC2) coordinate cholesterol egress from late endosomes-lysosomes (LE/LY). Proper folding, trafficking, and localization of both NPC proteins are essential for normal LE/LY cholesterol handling. Accordingly, mutations in NPC genes cause Niemann–Pick type C (NPC) disease, a progressive neurodegenerative lysosomal cholesterol storage disorder. The routes by which NPC1 reaches the LE/LY compartment in mammalian cells are not fully elucidated. Therefore, to interrogate NPC1 trafficking, we developed genome-engineered HeLa cells expressing endogenous NPC1 mNeon . We demonstrate that endogenous NPC1 localizes to the LE/LY compartment and by using protein proximity-based approaches that NPC1 resides in the same membranes as Vacuolar Protein Sorting-associated protein 41 (VPS41), one of the two unique subunits of the homotypic fusion and vacuole protein sorting complex. Loss of VPS41 increases NPC1 and Lysosomal Associated Membrane Protein 1 (LAMP1) abundance. Paradoxically, this results in marked accumulation of lysosomal cholesterol and induction of sterol regulatory element-binding protein signaling. Mechanistically, using immuno-fluorescence and electron microscopy imaging in combination with a VPS41-dependent ectopic recruitment assay, we demonstrate that this is due to a shift in the localization of NPC1 and LAMP1 from LE/LY to biosynthetic vesicles called LAMP carriers. These vesicles have been recently described to transport lysosomal-destined cargo directly from the trans- Golgi (TGN) network to LE/LY. In conclusion, we identify NPC1 as a cargo for VPS41-dependent LAMP carriers that are instrumental for the delivery of NPC1 to LE/LY and maintaining cellular cholesterol homeostasis.